Embedding Ecological Awareness Values in the Social Studies Curriculum: Strengthening Sustainable Agrarian Identity Among Students in Rural Coffee Producing Areas - Dhimas, Amri; Sela Rahmawati; Zahra Yasifa Hasbullah; Sona Minasyan; Murad Hameed Abdullah (Journal Education Innovation (JEI), 2026)
This study aims to identify how ecological awareness values can be integrated into the social studies curriculum to sustainably strengthen agrarian identity in junior high school students in coffee producing areas in rural Indonesia. This research used a qualitative approach with a case study design. This research was conducted at SMPN 5 Tanggul, SMPN 6 Tanggul, and SMPN 7 Tanggul which are located in the coffee mountains of Jember Regency. The informants in this study were 23 junior high school students from coffee farming families, 4 social studies teachers, 3 school principals, and 6 coffee farmers. Data collection techniques were conducted with in-depth interviews, participant observation, and documentation. Data analysis techniques using qualitative interactive analysis which includes data collection, data reduction, data display, and conclusion drawing. The data validity technique used extended participation, observation persistence, and triangulation of sources and methods. The results of this study indicate that strengthening students' agrarian identity through the integration of agrarian values in the social studies curriculum is carried out contextually, able to increase student involvement and be able to foster a sense of pride in their agrarian identity as children of coffee farmers. In addition, teachers are also able to adapt to various challenges by adopting creative strategies, utilizing the surrounding nature as a social studies laboratory, utilizing local resources, and collaborating between schools, farming communities, and local governments to support agricultural sustainability and the preservation of local cultural heritage